Las etnias centroamericanas en la segunda mitad del siglo xx - Francisco Lizcano Fernández (Revista Mexicana del Caribe, 2004)
In this article seven ethnic categories (Indigenous, Mestiza, Criolla, Mulata,Creole, Garífuna and Asian) are distinguished in the seven countriesin which the Central American region is divided: Belize, Guatemala, ElSalvador, Honduras, Nicaragua, Costa Rica and Panama. Later, the ethniccomposition of each of such nations, of Central America as a whole andof the two zones in which this region is divided (the Pacific one and theCaribbean one) is settled down, considering the relative importance ofthe seven ethnic categories in each of these spaces